Single-cell analysis of [Ca2+]i signalling in sub-fertile men: characteristics and relation to fertilization outcome. Issue 6 (25th April 2018) - Kelly, Mark C; Brown, Sean G; Costello, Sarah M; Ramalingam, Mythili; Drew, Ellen; Publicover, Stephen J; Barratt, Christopher L R; Martins Da Silva, Sarah
Abstract: STUDY QUESTION: What are the characteristics of progesterone-induced (CatSper-mediated) single cell [Ca 2+ ]i signals in spermatozoa from sub-fertile men and how do they relate to fertilizing ability? SUMMARY ANSWER: Single cell analysis of progesterone-induced (CatSper-mediated) [Ca 2+ ]i showed that reduced progesterone-sensitivity is a common feature of sperm from sub-fertile patients and is correlated with fertilization rate. WHAT IS KNOWN ALREADY: Stimulation with progesterone is a widely used method for assessing [Ca 2+ ]i mobilization by activation of CatSper in human spermatozoa. Although data are limited, sperm population studies have indicated an association of poor [Ca 2+ ]i response to progesterone with reduced fertilization ability. STUDY DESIGN, SIZE, DURATION: This was a cohort study using semen samples from 21 donors and 101 patients attending the assisted conception unit at Ninewells Hospital Dundee who were undergoing ART treatment. Patients were recruited from January 2016 to June 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: Semen donors and patients were recruited in accordance with local ethics approval (13/ES/0091) from the East of Scotland Research Ethics Service (EoSRES) REC1. [Ca 2+ ]i responses were examined by single cell imaging and motility parameters assessed by computer-assisted sperm analysis (CASA). MAIN RESULTS AND THE ROLE OF CHANCE: For analysis, patient samples were divided into three groups IVF(+ve) (successful fertilization; 62 samples), IVF-FF (failed fertilization; eight samples) and ICSI (21 samples). A further 10 IVF samples showed large, spontaneous [Ca 2+ ]i oscillations and responses to progesterone could not be analysed. All patient samples loaded with the [Ca 2+ ]i -indicator fluo4 responded to progesterone stimulation with a biphasic increase in fluorescence (transient followed by plateau) which resembled that seen in progesterone-stimulated donor samples. The mean normalized response (progesterone-induced increase in fluorescence normalized to resting level) was significantly smaller in IVF-FF and ICSI patient groups than in donors. All samples were further analysed by plotting, for each cell, the relationship between resting fluorescence intensity and the progesterone-induced fluorescence increment. In donor samples these plots overlaid closely and had a gradient of ≈ 2 and plots for most IVF(+ve) samples closely resembled the donor distribution. However, in a subset (≈ 10%) of IVF(+ve) samples, 3/8 IVF-FF samples and one-third of ICSI samples the gradient of the plot was significantly lower, indicating that the response to progesterone of the cells in these samples was abnormally small. Examination of the relationship between gradient (regression coefficient of the plot) in IVF samples and fertilization rate showed a positive correlation. In IVF-FF and ICSI groups, the proportion of cells in which a response to progesterone could be detected was significantly lower than in donors and IVF (+ve) patients. Approximately 20% of cells in donor, IVF(+ve) and ICSI samples generated [Ca 2+ ]i oscillations when challenged with progesterone but in IVF-FF samples only ≈ 10% of cells generated oscillations and there was a significantly greater proportion of samples where no oscillations were observed. Levels of hyperactivated motility were lower in IVF(+ve) and IVF-FF groups compared to controls, IVF-FF also having lower levels than IVF(+ve). LIMITATIONS, REASONS FOR CAUTION: This is an in vitro study and caution must be taken when extrapolating these results in vivo . WIDER IMPLICATIONS OF THE FINDINGS: This study reveals important details of impaired [Ca 2+ ]i signalling in sperm from sub-fertile men that cannot be detected in population studies. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by a MRC project grant (MR/M012492/1; MR/K013343/1). Additional funding was provided by Chief Scientist Office/NHS research Scotland.